2002
DOI: 10.1038/emm.2002.40
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular trafficking and metabolic turnover of yeast prepro-α-factor-SRIF precursors in GH3 cells

Abstract: Chimeric genes coding for prepro region of yeast α α α α-factor and anglerfish SRIF were expressed in rat GH 3 cells to determine whether yeast signals could regulate hormone processing in mammalian cells. We report that nascent hybrid polypeptides were efficiently targeted to ER, where cleavage of signal peptides and core glycosylation occurred, and were localized mainly in Golgi. These data indicate that prepro region of yeast α α α α-factor functions in sorting molecules to secretory pathway in mammalian ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Commonly used as a secretory peptide (Brake, 1984;Kjaerulff and Jensen, 2005;Lee et al, 2002;Oka et al, 1999), the alpha mating factor 1 secretory leader (MFa1pp) is made of two distinct pieces: the pre region and the pro region. The first 19 residues make up the pre region that serves to direct the nascent polypeptide to the endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used as a secretory peptide (Brake, 1984;Kjaerulff and Jensen, 2005;Lee et al, 2002;Oka et al, 1999), the alpha mating factor 1 secretory leader (MFa1pp) is made of two distinct pieces: the pre region and the pro region. The first 19 residues make up the pre region that serves to direct the nascent polypeptide to the endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…The MFa1pp is commonly used to direct the secretion of a number of different heterologous proteins in a number of hosts including Saccharomyces cerevisiae, Schizosaccharomyces pombe, Pichia pastoris, and mammalian cells, and its success as a secretory leader depends a great deal on the protein being directed (Kjaerulff and Jensen, 2005;Lee et al, 2002;Oka et al, 1999). Secretory leaders have previously been engineered by iterative processes of rational design and empirical optimization, specifically for the secretion of insulin precursor.…”
Section: Introductionmentioning
confidence: 99%
“…SAD may also affect organelles such as mitochondria, ribosome and endoplasmic reticulum, for pituitary adenoma cells have activity in synthesis and secretion of many kinds of hormones and abundance of organelles. It is reported that many important factors that regulate the expression of GH were synthesized and secreted in endoplasmic reticulum and Golgi such as Somatotropin release inhibiting factor (SRIF) (33), vascular endothelial growth factor (VEGF) (34), carboxypeptidase D (CPD) (35). SAD may indirectly influence these factors to reduce the expression of GH.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic signal peptides and leader sequences have been used extensively in yeast expression systems to enhance heterogeneous protein production (Brake et al, ; Heiss et al, ; Hou et al, ; Rakestraw et al, ). Use of the yeast mutant alpha mating factor 1 leader peptide (MFα1pp) in mammalian cells (rat pituitary‐derived cell line) resulted in efficient ER‐Golgi translocation of a neuropeptide (somatostatin), but led to inefficient processing and intracellular accumulation during later stages of the secretory pathway (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%